KESADARAN HUKUM MASYARAKAT PENGGUNA JALAN DI KOTA DENPASAR - TAGEL, DEWA PUTU (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 2 No 2 (2013), 2013)
Legal awareness of road users especially users of motorcycles is a process of assessment of the traffic law. Every human being has the legal awareness, the problem is the level of awareness, there is a high, medium and low. Based on the theory of legal awareness Soerjono Soekanto and research results in the field, it is known that the level of legal awareness of road users is relatively low, it can be seen from the understanding and behavior towards traffic rules. Legal System Theory from Lawrence M. Friedman and theory of Law Effectiveness Soerjono Soekanto used to determine the factors that affect the level of legal awareness. Based on this research, the factors that influence is divided into 4 parts, namely legal substance, legal structure, legal culture, and facilities. In accordance with the purposes of the law as social control, the police efforts are divided into 3 as pre-emptive, preventive and repressive realized through engineering of the traffic infrastructure, construction elements of road users, and engineering in the field of law or settings including law enforcement.
Keywords: Legal Awareness; Road Users; Traffic